Gambaran Timbang Terima Pasien Covid-19 di Rumah Sakit Dr. Bratanata Kota Jambi tahun 2021/2022 - Yemima Angel Lorence; Andi Subandi; Tuti Aryani (UIMA Press, 2022)
Background: Handover is the transfer of responsibility carried out by the shift implementing nurse and then given to the other person in charge using the SBAR technique. The importance of the SBAR technique in handover to reduce malpractice due is to unclear communication, improve teamwork, improve patient safety, and provide complete information on patient conditions. Objectives: Known process of handover by a nurse on a covid-19 patient at “B” hospital in 2021/2022. Methods: This research is quantitative research with the type of observational description study with a cross-sectional approach. The instruments used were handover checklist sheets and knowledge questionnaire sheets. Results: Implementation of the SBAR technique handover on covid-19 patients at “B” hospital Jambi did not perform well with Situation points of 75.4%, from 7 checklist points it was known that nurses were able to mention the patient's name (100%), the day of treatment, and the treating doctor (95.5%), medical diagnosis (100%), and complaints. main patient (81.8%) with good category. The background point is 49.35%, and it is shown that nurses are less able to explain nursing interventions that have been carried out, the patient's allergy history, and the patient's disease history. Point Assessment is 30.3%, of the six highest checklist points, nurses who can mention the patient's vital signs (81.8%) and elimination abilities (95.5%) are in a good category. Point Recommendation (36.6%) of the three points of the nurse checklist provides recommendations for nursing interventions that have been and need to be continued (95.5%). This is supported by the results of the nurse's SBAR technique handover knowledge, namely 59.32% (Know enough). Conclusion: Based on the results of the research on the implementation of the weigh-in of Covid-19 patients at “B” hospital went poorly with the best aspect at the Situation point of 75.4%, supported by the knowledge of nurses about weighing and receiving, namely 59.32% which was included in the category of Sufficient Know